Isolation of a photosystem II reaction center consisting of D-1 and D-2 polypeptides and cytochrome b-559 - Nanba, Osamu (1987)
A photosystem II reaction center complex consisting of D-1 and D-2 polypeptides and cytochrome b-559 was isolated from spinach grana thylakoids, treated with 4% (wt/vol) Triton X-100, by ion-exchange chromatography using DEAE-Toyopearl 650S. The isolated complex appears to contain five chlorophyll a, two pheophytin a, one β-carotene, and one or two cytochrome b-559 heme(s) (molar ratio) and exhibits a reversible absorbance change attributable to the photochemical accumulation of reduced pheophytin typical for the intermediary electron acceptor of photosystem II reaction center. These results strongly suggest that the site of primary charge separation in photosystem II is located on the heterodimer composed of D-1 and D-2 subunits.